الفروق في الأتجاهات نحو مهنة معلمة الروضة لدى طالبات برنامج تربية الطفل في ضوء بعض المتغيرات الديموغرافية بكلية إربد الجامعية - الصلاحين، عبدالكريم محمود (جامعة الأزهر - كلية التربية, 2016)
هدفت الدراسة الكشف عن اتجاهات طالبات برنامج تربية الطفل بكلية إربد الجامعية نحو مهنة معلمة الروضة، وعلاقة ذلك بفرع الثانوية العامة، والمعدل في الثانوية العامة، وعمل أحد أفراد الأسرة في مهنة التعليم، ومستوى دخل الأسرة، ولتحقيق أهداف الدراسة تم تطوير استبيان تكون من جزأين: تضمن الأول المعلومات الشخصية للطالبة، وتضمن الجزء الثاني (23) فقرة عن الاتجاه نحو مهنة معلمة الروضة، وأظهرت النتائج اتجاهات إيجابية مرتفعة لدى الطالبات نحو مهنة معلمة الروضة، كما أظهرت فروقا دالة إحصائيا تعزى لمتغير فرع الثانوية العامة، ولم تظهر فروق دالة إحصائيا تعزى لمتغيرات: المعدل في الثانوية العامة، وعمل أحد أفراد الأسرة في مهنة التعليم، ومستوى دخل الأسرة، وفي ضوء النتائج قدمت الدراسة عددا من التوصيات الإجرائية.
The study aimed at detecting the attitude of female students of child-rearing Program at the Irbid University College towards the profession of kindergarten teacher, and its relationship to the high school stream and grade, the work of a family member in the teaching profession, and the level of family income. In order to achieve the objectives of this study, a two-part questionnaire was developed. The first part included the female student’s personal information, while the second part included (23) paragraphs about the trend toward the profession of kindergarten teacher. The results showed high positive trends among female students toward the profession of kindergarten teacher. They also showed significant differences due to the variable high school stream. However, no statistically significant differences were attributable to the following variables: high school grade, the work of a family member in the teaching profession, and the level-of family income. In light of the study results, a number of procedural recommendations were suggested.
Keywords: معلمات الروضة -- تربية الأطفال -- الطالبات المعلمات -- التأهيل المهنى -- كلية إربد الجامعية